Exploring the Potency of Learning Together Strategy in Improving Secondary School Students Attitude towards Civic Education - Abayomi , Akapo Tijani; Shekoni, Lateef Kehinde; Olanrewaju, Lawal Ismail; Bolanle, Akeusola Nafisat (FKIP - Universitas Riau, 2025)
Learning Together strategy structures instructional activities around principles such as positive interdependence, individual accountability, promotive face-to-face interaction, social and collaborative skills, and group processing. This study examined the efficacy of learning together strategy on secondary school students’ attitude towards civic education. Quasi-experimental design, pretest-post-test control group design was employed. A total of 102 SS II students in two intact classes, located in two senatorial districts in Lagos State, participated in the study. Civic Education Attitude Questionnaire (CEAQ) with a reliability coefficient of 0.80 was used for data collection. Data collected were analysed using mean, standard deviation and ANCOVA. It was revealed that a statistically significant difference exists in the attitude of the students in the learning together and conventional lecture group, in favour of the earning together group [F(1, 100) = 7.99; p < 0.05].Also, there was no differential impact of gender on the attitude of students taught using learning together strategy. It was concluded that learning together is a potent strategy for enhancing students’ attitude towards civic education.